2021
DOI: 10.3389/fcell.2021.701788
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis and Its Potential Role in Metabolic Diseases: A Curse or Revitalization?

Abstract: Ferroptosis is classified as an iron-dependent form of regulated cell death (RCD) attributed to the accumulation of lipid hydroperoxides and redox imbalance. In recent years, accumulating researches have suggested that ferroptosis may play a vital role in the development of diverse metabolic diseases, for example, diabetes and its complications (e.g., diabetic nephropathy, diabetic cardiomyopathy, diabetic myocardial ischemia/reperfusion injury and atherosclerosis [AS]), metabolic bone disease and adrenal inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 276 publications
(258 reference statements)
0
28
0
Order By: Relevance
“…The strongest finding from the sample group comparison was 'Alpha-Linoleic acid metabolism', which is supported by Overgaard et al as they showed the deregulation of diglyceride in early states of the type 1 diabetes progression (Overgaard et al 2016). The second strongest detection was 'Ferroptosis', referring to iron-dependent regulated cell death, which was identified only 10 years ago and is currently under intensive study; it has already been linked to the development of metabolic diseases (Duan et al 2021). The pathway 'Th1 and Th2 cell differentiation' has been strongly linked to development of T1D (Walker et al 2016, Bradley et al 1999.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The strongest finding from the sample group comparison was 'Alpha-Linoleic acid metabolism', which is supported by Overgaard et al as they showed the deregulation of diglyceride in early states of the type 1 diabetes progression (Overgaard et al 2016). The second strongest detection was 'Ferroptosis', referring to iron-dependent regulated cell death, which was identified only 10 years ago and is currently under intensive study; it has already been linked to the development of metabolic diseases (Duan et al 2021). The pathway 'Th1 and Th2 cell differentiation' has been strongly linked to development of T1D (Walker et al 2016, Bradley et al 1999.…”
Section: Resultsmentioning
confidence: 72%
“…2016). The second strongest detection was ‘Ferroptosis’, referring to iron-dependent regulated cell death, which was identified only 10 years ago and is currently under intensive study; it has already been linked to the development of metabolic diseases (Duan et al . 2021).…”
Section: Resultsmentioning
confidence: 99%
“…During the past decades, there has been an accumulative research focus on the relationship between ferroptosis and diseases [ 75 , 76 ]. The significance of ferroptosis in cell survival and differentiation is widely accepted, and its regulatory role in the modulation and treatment of diverse disease has been gradually uncovered [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, CD is pivotal for internal homeostasis and prevention of CCVDs ( Duan et al, 2021 ). Ferroptosis is accompanied by iron overload, excess lipid peroxidation and a large amount of ROS production, which can accelerate a collection of pathological processes such as inflammation, mitochondrial dysfunction, ERS, and OS that further lead to the increase of CD and damage to the normal function of cardio-cerebral vessels.…”
Section: The Mechanism Of Ferroptosismentioning
confidence: 99%